Association between offspring intelligence and parental mortality: a population-based cohort study of one million Swedish men and their parents. Issue 8 (11th July 2008) - Modig-Wennerstad, K; Silventoinen, K; Batty, D; Tynelius, P; Bergman, L; Rasmussen, F
Abstract : Background: An inverse association of IQ with mortality has been observed in previous studies. Analyses of associations between offspring's IQ and parental mortality in biological and non-biological family relations may shed light on genetic and environmental influences. Methods: In a target cohort of 1 235 375 Swedish men, 931 825 (75%) men had complete data on all variables used. IQ of offspring was measured at age 18 and mothers and father were followed, on average, for 21.2 years and 19.7 years, respectively, with respect to all-cause and cause-specific mortality (cardiovascular disease, coronary heart disease, stroke and diabetes). The analyses were conducted by proportional hazards regression with adjustment for parental occupation, education and income. Results: In adjusted analyses using IQ as a continuous variable over a standard nine-point scale, hazards ratio (HR) for all-cause mortality was 0.96 (95% CI 0.96 to 0.96) for fathers and 0.95 (0.95 to 0.95) for mothers. The corresponding HRs were 0.99 (0.97 to 1.00) for step-fathers and 0.97 (0.95 to 0.99) for step-mothers. In adjusted analyses, HRs for CVD mortality among fathers and mothers were 0.97 (0.96 to 0.97) and 0.94 (0.93 to 0.94) respectively. The corresponding HRs for diabetes mortality were 0.91 (0.89 to 0.92) among fathers and 0.85 (0.83 to 0.87) among mothers. Conclusions: The associations found in non-biological family relationships suggest shared environmental influences and/or assortative mating. Stronger IQ-mortality associations in biological than non-biological relationships suggest genetic influences. Stronger inverse offspring IQ–parental mortality associations in mothers than in fathers might be due to environmental factors or epigenetic mechanisms.